High-resolution imaging transit photometry of Kepler-13AB - Howell, Steve B.; Scott, Nicholas J.; Matson, Rachel A.; Horch, Elliott P.; Stephens, Andrew (The Astronomical Journal, 2019)
Using the high-resolution imaging instrument, 'Alopeke, at the Gemini-N telescope, we obtained simultaneous two-channel time-series observations of the binary exoplanet host star Kepler13-AB. Our optical observations were obtained during a transit event of the exoplanet Kepler-13b and light curves were produced using both speckle interferometric and aperture photometry techniques. Both techniques confirm that the transiting object orbits the star Kepler-13A while different transit depths are seen across the optical wavelength range, being ∼2 times deeper in the blue. These measurements, as well as mass determinations in the literature, are consistent with Kepler-13b being a highly irradiated gas giant with a bloated atmosphere. Our observations highlight the ability of high-resolution speckle imaging to not only assess binarity in exoplanet host stars but robustly determine which of the stars the transiting object actually orbits. © 2019. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-359-450-283-875, pop00155 tex.type: [object Object]
Keywords: binaries: close; dept.phy; galaxies: photometry; instrumentation: high angular resolution; peer-reviewed; planetary systems; techniques: image processing

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-502-692-786-428, pop00025 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric